(untitled) (The Research of Medical Science Review, 2024)
Microplastics—small plastic particles less than 5 mm—have grown to be a major environmental problem due to their persistence and widespread presence. This review looks at the primary sources of microplastics, including sources like industrial particles and secondary sources that result from the breakdown of larger plastic waste. From the physical harm they do to aquatic life to the bioaccumulation of dangerous compounds in food chains, microplastics have a substantial detrimental impact on both the environment and human health. Additionally, highlighted are the potential health risks associated with chemical exposure, ingestion, and inhalation. Numerous remediation techniques, including bioremediation methods, technological developments, cleanup campaigns, and preventative measures, are presented to solve this expanding issue. Despite tremendous advancements, Effective management is hindered by microplastic detection, quantification, and regulation. To lessen the negative effects of microplastic pollution on the environment and human health, this review highlights the importance of tackling the problem and the necessity of interdisciplinary cooperation and creative solutions.